British Draft Resolution of Situation in Cyprus in 1957-1958: “Macmillan’s Plan” - A. G. Nesterov; M. I. Zlatoustova (Научный диалог, 2017)
The status of Cyprus in the late 1950-ies as well as the UK policy associated with the solution of the Cyprus problem are discussed. On the basis of British documents and sources on USA foreign policy of the mid-20th century an overview of British foreign policy in relation to controlled island is made. Special attention is paid to project of the Prime Minister of Great Britain Harold Macmillan, according to which the status of Cyprus were to remain unchanged for seven years, and the Greek Cypriots and the Turkish Cypriots could participate in the political life of the island through new organs of power, functioning separately for each community. The approach of foreign Minister and later Prime Minister of Great Britain H. Macmillan is analysed to normalization of the situation in Cyprus in the second half of 1950-ies, complicated as a result of national liberation struggle of the Greek Cypriots unfolding on the island, who supported the idea of enosis (a movement for annexation to Greece). Also the main problems and disagreements in the positions of Turkey, Greece and the UK on certain articles of Macmillan draft are highlighted. The number of the articles are considered on the emergence of new authorities and distribution of powers between the Governor of the island and government authorities.